Odpowiedź :
Odpowiedź:
5 ( 3-2x) = 15 -10x
3 - 4 ( x+6)= 3-4x -24= -4x- 21
( 20 -4x) :4= 5-x
4( -5-6y) + ( 2y+5)= -20 -24y +2y +5= -22y -15
( 10x -12y +6) :2= 5x -6y +3
( 3a + 3 ) *4 - ( 2a -10)= 12a +12 -2a +10= 10a +22
Szczegółowe wyjaśnienie:
Odpowiedź:
1. 5 (3 - 2x) = 15 - 10x
2. 3-4 (x + 6) = -1(x + 6) = -x - 6
3. (20 - 4x) ÷ 4 = 5 - x
4. 4(-5 - 6y) + (2y + 5) = 4*-5-6y+2y+5= 20-24y + 2y + 5 = 15 - 22
5. (10x - 12y + 6) ÷ 2 = 5x - 6y + 3
6. (3a - 3) * 4 - (2a - 10) = 3a - 3 * 4 - 2a + 10 = 12a - 12 - 2a + 10 = 10a - 2
Szczegółowe wyjaśnienie:
Chyba tak